PSYCHOLOGICAL CONTRACT BREACH AND ITS IMPACT ON EMPLOYEE LOYALTY AND INTENTION TO STAY - Indria Sri Retnaningrum; Dhenny Asmarazisa; Catur Fatchu Ukhriyawati (RADJA PUBLIKA, 2025)
This study examines the impact of Psychological Contract Breach (PCB) on employee intention to stay, investigating the mediating role of employee loyalty. Based on social exchange theory, we hypothesized that PCB would negatively impact retention intentions both directly and indirectly through eroded loyalty. Data were collected via a cross-sectional survey from a sample of employees across various industries. The results, analyzed using structural equation modeling, confirmed that PCB is a significant negative predictor of intention to stay. Furthermore, employee loyalty fully mediated this relationship, revealing that the primary mechanism through which PCB influences turnover is by damaging the emotional bond and allegiance employees feel toward the organization. The findings highlight that the breach of implicit agreements triggers a destructive affective process. Practical implications suggest managers must actively manage psychological contracts through transparent communication and trust-building to foster loyalty and retain talent.